The Role of Economics of Leningrad in the Soviet National Industry During The Great Patriotic War - Anastasia V. Zotova (International Review of Management and Marketing, 2016)
This article is based on archival documents and published sources the role of Economics in Leningrad All-Union economy during the Great Patriotic war was described. It is emphasized that even in the enemy siege the residents of Leningrad have provided the front with everything necessary. There were data on losses of the enterprises of Leningrad during the war, as well as information about the damage to the city utilities, transportation, and communications. The author paid attention to the study of the dynamics of evacuation equipment and specialists from Leningrad during 1941-1943 and process of re-evacuation occurred in 1944. An attention was payed to the qualitative changes in the structure of the equipment that was associated with the selection of new production technologies. This article examined a wide range of economic issues, including the development of multiple industries as well as the activities of the health care system, public education and cultural institutions. Attention was drawn to the fact that all operated in Leningrad enterprises and institutions was a single state-owned facility. Special attention was paid to the activities of the banking system, its role in the maintenance of municipal enterprises, institutions and people of Leningrad.